2011
DOI: 10.1111/j.1600-0668.2010.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal comfort conditions in a classroom with three ventilation methods

Abstract: The confirmation of the significantly elevated thermal neutral temperature can have a number of implications for both thermal comfort in an air-conditioned room and energy consumption of the associate air-conditioning system. With respect to the former, it provides scientific basis for the feasibility of elevated room temperatures, and with respect to the latter, it reveals considerable potentials for energy saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 9 publications
6
48
0
Order By: Relevance
“…It appears that low ventilation is related to both perceived poor air quality and high indoor temperature, which has also been reported in other studies [17,26,40].…”
Section: * Correlation Is Significant At the 005 Level (2-tailed) *supporting
confidence: 86%
See 1 more Smart Citation
“…It appears that low ventilation is related to both perceived poor air quality and high indoor temperature, which has also been reported in other studies [17,26,40].…”
Section: * Correlation Is Significant At the 005 Level (2-tailed) *supporting
confidence: 86%
“…Recent studies have also reported associations between inadequate ventilation and learning outcomes [13][14][15][16]. In addition to improved IAQ, proper classroom ventilation could also improve thermal comfort [17,18].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…4). This finding is in good agreement with the previous result [35], where the neutral temperature of about 27 C was obtained. Especially, under 10 ACH and the room temperature of 27 C, the subjects sat at Seat No.…”
Section: Thermal Sensation and Comfortsupporting
confidence: 95%
“…Although Zhang et al [13] and Fong et al [14] concluded that having an acceptable thermal environment from a well-designed UFAD system is possible.…”
Section: Introductionmentioning
confidence: 99%